2017
DOI: 10.1111/jan.13464
|View full text |Cite
|
Sign up to set email alerts
|

Systematic psychometric review of self‐reported instruments to assess patient safety culture in primary care

Abstract: The findings of the present review suggest that the SCOPE-Primary Care survey is the most appropriate tool to assess patient safety culture in primary care. Further psychometric techniques are now essential to ensure that the instrument provides meaningful information regarding safety culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Particular staff safety climate survey with the most evidence of validity and reliability were the PC SafeQuest, Frankfurt Patient Safety Climate Questionnaire (FraSiK) and SCOPE. It was suggested that rather than developing new surveys, researchers should focus on improving the psychometric properties of existing tools [ 15 , 24 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particular staff safety climate survey with the most evidence of validity and reliability were the PC SafeQuest, Frankfurt Patient Safety Climate Questionnaire (FraSiK) and SCOPE. It was suggested that rather than developing new surveys, researchers should focus on improving the psychometric properties of existing tools [ 15 , 24 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…One review [ 16 ] included a study concerned with identifying lessons learned from error, and another review included studies on the use of safety culture data to inform risk management and feedback in order to inform improvement efforts [ 19 ]. A number of the reviews also concluded that safety data should be used to inform patient safety improvement [ 16 , 19 ], and there was a need to triangulate safety data from multiple sources [ 15 , 20 , 21 , 26 , 27 ]. However, it was suggested that the recruitment of patients to complete patient report measures may add another layer of difficulty that may reduce the use of such measures [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing the quality of hospital services by improving patient safety culture is an increasing focus of practical action and research interest in health systems. 1 2 The quality of health services can be improved through embedding a safe and reliable culture, supported by managers who understand its influence on organisational performance, including clinical outcomes. 3 4 However, there is limited literature investigating the interaction between patient safety culture and patient experience, unlike the extensive research on these concepts individually.…”
Section: Introductionmentioning
confidence: 99%
“…The Joint Commission describes safety culture as a healthcare organization’s values, commitment, competencies, and actions in pursuit of patient safety [ 1 ]. Validated safety culture surveys exist for patients and providers in hospitals, pharmacies, nursing homes, and medical offices [ 6 , 7 ]. But patient safety survey implementation has lagged within academic settings [ 8 ], including programs that provide training in spinal manipulative therapy (SMT).…”
Section: Introductionmentioning
confidence: 99%